PENGARUH PEMBERIAN PUPUK ORGANIK CAIR LIMBAH BATANG PISANG TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT (Lycopersicum esculentum Mill) VARIETAS SERVO F-1 - Ainy Qomariah Manurung (UNIVERSITAS LABUHANBATU, 2015)
This study aims to determine the effect of liquid organic fertilizer on banana stem waste on the growth and production of tomato plants (Lycopersicum esculentum Mill). This research was carried out in the form of field experiments conducted in Pinang Lombang Upper Village, NA IX-X District, North Labuhanbatu Regency. This study was prepared using Randomized Block Design (RBD) with 5 (five) treatments, namely O0 = Control, O1 = 200 ml, O2 = 300 ml, O3 = 400 ml, and O4 = 500 ml. Each replication has 40 plant samples, so the total sample is 120 plants. Parameters observed were: Plant height, number of leaves, stem diameter, and weight of fresh fruit. Data were analyzed using the F test then followed by tukey test. The results showed that the best treatment was to use 400 ml of liquid organic fertilizer banana / plant stem waste. Keywords: banana stem, Lycopersicum esculentum, organic fertilizer